Foreign aid and female empowerment - Maria Perrotta Berlin; Evelina Bonnier; Anders Olofsgård (Stockholm School of Economics, Stockholm Institute of Transition Economics (SITE), 2023)
We estimate the community-level impact of foreign aid projects on women's empowerment in the country with the most complete recent record of geo-coded aid project placement, Malawi. Our estimates can thus be interpreted as the average impact of aid from many different donors and diverse projects. We find that aid in general has a positive impact, in particular on an index of female agency and women's sexual and fertility preferences. Gender-targeted aid has a further positive impact on women's sexual and fertility preferences, and more tentatively on an index focusing on gender-based violence. However, the positive impact of gender-targeted aid disappears in patrilineal communities, and men's attitudes towards female agency in the areas of sexuality and fertility are even negatively affected. This suggests that donors need to consider that the impact of aid on female empowerment can depend on the community context when they decide on aid project design and placement.
Keywords: 330; foreign aid; gender; development; geo-coded data; impact analysis